Analysis of the effects of climbing in the reproductive biology of the bearded vulture (Gypaetus barbatus L.) in the central Pyrenees (Aragon - Spain) - Blasco Ibáñez, Ignacio; Longares Aladrén, Luis Alberto; Gil Gallús, Juan Antonio (Geographicalia, 2015)
Within all bird of prey natural populations exist reproductive units (UR), whose productivity, understood as juveniles flown a year, is low or none. The effects of human disturbance in nesting areas has been one of the mostly related reasons with the decrease of productivity of many birds of prey (Richarson y Miller, 1997). According to Arroyo y Razin (2006), human activity nearby Bearded vulture nests (Gypaetus barbatus L.) can negatively affect reproduction. Current recovery plans for this spice in place in the Pyrenees range, include specific measures in order to avoid reproductive failure, by mean of the application of preventing measures for disturbing factors: hunting, sport climbing. During the last 10 years climbing in Aragon (across all varieties), has experienced an increase in number of people and sectors where it’s practiced. With the aim of knowing potential impacts of rock climbing in the conservancy of Bearded vulture information regarding climbing zones in the province of Huesca has been compiled. Afterwards, such information has been georeferrenced and different geospatial methodologies with GIS techniques in the ArcGis environment had been applied. The objective has been taking a close approach of the analysis of the posible correlation effect between climbing and nesting of this specie. Out of a total of 315 Bearded vulture nest in Aragon (2011), it has been proven that 11,75% (n = 37) could had been affected by climbing sports.